The methodological paths for the study of sanitary surveillance - Regina Célia Borges de Lucena (Universidade de Fortaleza, 2013)
Objective: The aim is to assess the appropriateness of using quantitative and qualitative approaches to analyzing and understanding the sanitary surveillance object in its relation to epidemiology. Data Synthesis: After a brief background on the relationship between epidemiology and social sciences, and between quantitative and qualitative methods, the study analyzes characteristics of the sanitary surveillance object that may assist the understanding of its nature and, therefore, of the most appropriate methodological approaches to its analysis. The characteristics identified here - namely, complexity of health/disease process, concept of risk, performance in promotion and protection levels, sanitary surveillance management model, availability of information, and relationship with epidemiology - express quantitative and qualitative aspects of equal importance to the knowledge of this issue. Conclusion: The combination or interaction of quantitative and qualitative approaches can be considered, in the case of sanitary surveillance, as a vital requisite for the apprehension of this object in its entirety.